Trifluridine/tipiracil with or without bevacizumab in metastatic colorectal cancer: results of a systematic review and meta-analysis - Takayuki Yoshino; Julien Taieb; Yasutoshi Kuboki; Per Pfeiffer; Amit Kumar; Howard S. Hochster (Therapeutic Advances in Medical Oncology, 2023)
Background: Trifluridine/tipiracil plus bevacizumab (FTD/TPI + BEV) has shown efficacy and tolerability in refractory metastatic colorectal cancer (mCRC). Because randomized controlled trial (RCT) data comparing FTD/TPI + BEV with FTD/TPI are lacking, this meta-analysis evaluated outcomes with both regimens. Data Sources and Methods: Electronic databases, congress proceedings (past 3 years), trial registries, systematic review bibliographies, gray literature, and guidelines through June 2021 were searched for RCTs, non-RCTs, and prospective observational studies involving >20 previously treated patients with mCRC receiving FTD/TPI + BEV or FTD/TPI. Absolute and relative disease control rate (DCR), progression-free survival (PFS), overall survival (OS), adverse event (AE) rates, and discontinuation rates due to AEs were evaluated using fixed-effects and random-effects models. Study quality, heterogeneity, and publication bias were assessed. Results: In all, 29 of 875 screened publications were selected (26 studies: 5 RCTs, 11 non-RCTs, and 10 prospective observational studies). One RCT compared FTD/TPI + BEV with FTD/TPI. FTD/TPI + BEV versus FTD/TPI had a higher absolute DCR [64% (6 studies; n  = 289) versus 43% (10 studies; n  = 2809)], median PFS [4.2 (5 studies; n  = 244) versus 2.6 (6 studies; n  = 1781) months], 12-month PFS [9% (5 studies; n  = 244) versus 3% (6 studies; n  = 1781)], median OS [9.8 (5 studies; n  = 244) versus 8.1 (6 studies; n  = 1814) months], and 12-month OS [38% (5 studies; n  = 244) versus 32% (6 studies; n  = 1814)]. Grade ⩾3 febrile neutropenia, asthenia/fatigue, diarrhea, nausea, and vomiting rates were similar (1%–7%). Grade ⩾3 neutropenia rate was higher with FTD/TPI + BEV than with FTD/TPI [43% (6 studies; n  = 294) versus 29% (12 studies; n  = 7139)]. Discontinuation rates due to AEs were similar [8% (5 studies; n  = 244) and 7% (10 studies; n  = 3724)]. Low study quality, heterogeneity, and/or publication bias were detected in certain instances. Conclusion: Despite fewer patients treated with the combination, this meta-analysis consistently suggested that FTD/TPI + BEV provides benefits over FTD/TPI in refractory mCRC and has similar safety, except for more frequent grade ⩾3 neutropenia.